Systematic literature review: The impact of the STEAM learning approach on critical thinking skills in science education - Mislah Mislah; Siti Patonah; Intan Indiati; M. Syaipul Hayat; Joko Siswanto (Universitas PGRI Pontianak, 2025)
This study aims to systematically examine empirical evidence from the past five years regarding the impact of the Science, Technology, Engineering, Art, and Mathematics (STEAM) approach on students’ critical thinking skills at the primary and secondary education levels. A qualitative Systematic Literature Review (SLR) method was employed. The literature was collected via Google Scholar, focusing on publications from 2019 to 2024, using a combination of keywords in both Indonesian and English. Out of 98 articles initially identified, only ten were selected based on inclusion and exclusion criteria, and further assessed using the Joanna Briggs Institute Checklist for quality appraisal. Data were analyzed using thematic analysis, categorizing studies based on educational level, subject matter, learning models, research methods, instruments used, and research outcomes. The review findings indicate that approximately 90% of the studies reported a significant improvement in students’ critical thinking skills through the implementation of Project-Based Learning (PjBL) integrated with STEAM. The most substantial effects were observed at the senior high school level, particularly in Physics and Biology subjects. At the elementary level, the STEAM approach was more effective when combined with play-based or exploratory learning activities. In junior high schools (SMP and MTs), STEAM served as a bridge between foundational conceptual understanding and the development of analytical skills. These findings highlight that the effectiveness of STEAM is highly contextual and influenced by students’ cognitive readiness, teacher support, and the socio-economic conditions of schools. The study concludes that STEAM should not be viewed merely as a pedagogical strategy, but as an adaptive educational practice. Practical implications include the need for differentiated instructional strategies, equitable access to learning resources, and teacher training programs to support more widespread and equitable implementation.